Efficacy of cinnamon (Cinnamomum burmannii) extract to decrease serum creatinine in acute kidney injury induced male wistar rats - Evi Lusiana; Nia Savitri Tamzil; Desi Oktarina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Background Kidney vital function as a regulator of blood volume and chemical composition to excrete solute and water selectively. Acute kidney injury (AKI) is a sudden decline in kidney function which is temporary, is marked by an increase in serum creatinine levels and decreased urine output. Objective This study aims to determine the effectiveness of cinnamon extract in acute kidney injury induced male wistar rats. Method An experimental in vivo with pre-post control group design was conducted in twenty-five wistar strain white rats that were divided into 5 treatment groups that received methylprednisolone as a positive control, aquades, and different dose of cinnamon extracts (50 mg/kgBW, 100 mg/kgBW, and 200 mg/kgBW). The rat model of acute kidney injury was prepared by the method of unilateral ureteral obstruction (UUO). The effectiveness of cinnamon extract was carried out by creatinine levels checked using ELISA and analyzed by ANOVA. Results The extract of cinnamon can lower serum creatinine levels were significantly (p <0.05). A dose of 100mg / KgBW is an effective dose in AKI compare to methylprednisolone. Conclusion Extract of cinnamon (Cinnamomum burmannii) corrected creatinine levels of acute kidney injury induced male wistar rats. Keywords: Acute kidney injury, cinnamon extract, creatinine